Research on Key Technologies of Data Collection for Energy Storage Power Station Based on "Multi-Station Fusion". Issue 1 (November 2020) - Wang, Peng; Yang, Jinsong; Chen, Jing; Guo, Ruixiang; Yang, Desheng; Guo, Zheng
Abstract: In view of the current situation of energy storage power station management and data collection, this topic takes the data collection of energy storage power station as the main research object. By analyzing the problems of localized management and inconsistent data collection standards of energy storage power station, an efficient and accurate data collection and lean management mode is explored. It lays a foundation for promoting the construction of "Multi-Station fusion" and provides technical support for the management decision-making of "Multi-Station fusion".